Income Insecurity and Exclusion of Older Immigrant Women in Canada: A Narrative Review - Onuzulike, Ogeh Cynthia Onuzulike (African Journal of Stability and Development (AJSD), 2025)
In Canada, many older immigrants experience a lack of income security, shame, social exclusion, and social isolation due to insecure access to economic equity and redistribution. In addition, older immigrant women experience disproportionately high rates of income insecurity associated with feelings of shame and social isolation. This narrative review explores why the lack of income security is prevalent among the immigrant population and how financial instability could lead to feelings of shame, unwantedness, social exclusion, and social isolation. The analysis of the articles included in this review identified four themes: i. the mechanisms of income insecurity related to financial literacy; ii. shame, unwantedness, and social isolation associated with lack of income security for immigrant women; iii. women’s experiences with income insecurity and social exclusion; and iv. ageism, immigration, resistance, and resilience.